Meningkatkan Hasil Belajar Matematika Dengan Memanfaatkan Media E-Book Pada Mata Materi Barisan di Siswa Kelas XI SMA Negeri 22 Maluku Tengah - Haris Kolengsusu (Peneliti.net, 2022)
The purpose of this study was to find out how to improve mathematics learning outcomes by utilizing e-book media on the subject line in class XI students of SMA Negeri 22 Central Maluku. The research method used is classroom action research. The subjects in this Classroom Action Research (CAR) were class XI students at SMA Negeri 22 Central Maluku with a total of 24 students consisting of 10 boys and 14 girls. The technique used in collecting data in this study is a test and non-test technique. The test technique is used to determine student learning outcomes by using multiple choice questions. for each cycle there are 10 items with a maximum score of 100 and the non-test technique is used to measure the success of learning using the E-Book using observation sheets. Data on student learning outcomes that have been collected will be analyzed descriptively, namely by looking at the percentage of learning completeness, both classically and individually. Based on the results of research by utilizing e-book media in the subject matter of lineups in class XI students of SMA Negeri 22 Central Maluku, it tends to experience a significant increase, this is shown from the acquisition of the average final test score of cycle I reaching 66.67% and cycle II average the average reached 91.67%.